Determinan Volatilitas Harga Saham di Top 10 Konstituen 5-ASEAN - Sirullah, Alfi Alifi; Hanafi, Syafiq Mahmada (Universitas Negeri Surabaya, 2023)
This study was conducted to examine the factors that can affect stock price volatility in the Top 10 5-ASEAN Constituents before, and during the covid 19 pandemic (2018-2022 Period). Dividend policy, profitability, earning volatility, and assets growth are independent variables while stock price volatility is the dependent variable. The method used is panel data regression analysis. The test results found that dividend policy and earning volatility have no negative and significant effect on stock price volatility, while profitability has a negative and significant effect. Assets growth has a positive and significant effect on stock price volatility.